Entre a diplomacia e a historiografia: a visão de mundo de Hélio Lobo (1908-1939) - Pereira, Gabriel Terra [UNESP] (2013)
In the context of republicanization institutions and political actors in Brazil in the late nineteenth and early twentieth century, Brazilian diplomacy, led by reforms in the management of Rio Branco, intensified the process of Americanization, represented by the progressive approach to the countries of continent, notably the United States. Hélio Lobo (1883-1960), elected by the Chancellor in the wake of renewed frameworks of the Foreign Ministry, was an exponent of the policy of Americanization to work for political and legal understanding of American States on several occasions, such as the American Conference (1910 and 1923) and consulates in New York (1920-1926) and Montevideo (1926-1930). In parallel, the diplomat said the elaborate works of historical character, focusing on the Brazilian diplomacy and origin of Pan-Americanism throughout the nineteenth century. The dedication to this career and compliments the White River as the savior and representative of the golden age of Brazilian diplomacy, enabled him recognition necessary to join the IHGB and ABL, traditional strongholds of Brazilian intellectuals and where may publish new studies focused on the defense of Brazil. It is understood that Hélio Lobo was deeply committed to diplomacy oligarchies, characteristic of the First Republic, while the establishment of the Provisional Government in 1930 legitimized their output of the diplomatic corps. At the time, Hélio Lobo refused to buy and send ammunition to the government in Rio de Janeiro, which would use against the Paulistas-constitutional conflict in 1932. Attempts to return to the Foreign Ministry were not successful until 1960, when he died. At the end, we observe the trajectory of the diplomat-historian some relevant points that enable outline their worldview, namely the constant reference to the law as a legitimizing element of diplomatic negotiation - posture seen in the works of the Brazilian diplomatic history...